Comparing the radiological anatomy, electrophysiology, and behavioral roles of the pedunculopontine and subthalamic nuclei in the normal and parkinsonian brain - Aravamuthan, B; Bhooma Rajagopalan Aravamuthan (2008)
Deep brain stimulation (DBS) of the subthalamic nucleus (STN) and DBS of the pedunculopontine nucleus (PPN) have been shown to be effective surgical therapies for Parkinson’s disease (PD). To better understand the PPN and STN as DBS targets for PD, this research compares the anatomy, electrophysiology, and motor control roles of these nuclei. PPN and STN connections were examined in vivo in human subjects and in the non-human primate using probabilistic diffusion tractography. Both the PPN and STN were connected with each other and with the motor cortex (M1) and basal ganglia. After studying these anatomical connections in primates, their functional significance was further explored in an anesthetized rat model of PD. Examination of the electrophysiological relationship between the PPN and basal ganglia in the presence of slow cortical oscillatory activity suggested that excitatory input from the STN may normally modulate PPN spike timing but that inhibitory oscillatory input from the basal ganglia output nuclei has a greater effect on PPN spike timing in the parkinsonian brain. To examine transmission and modulation of oscillatory activity between these structures at higher frequencies, LFP activity was recorded from the PPN and STN in PD patients performing simple voluntary movements. Movement-related modulation of oscillatory activity predominantly occurred in the α (8-12 Hz) and low β (12-20 Hz) frequencies in the STN but in the high β (20-35 Hz) frequencies in the PPN, supporting observations from rodent studies suggesting that oscillatory activity is not directly transmitted from the STN to the PPN in PD. Finally, to better understand the roles of the STN and PPN in large-scale movement, the effects of STN and PPN DBS on gait abnormalities in PD patients were studied. DBS of the STN appeared to improve gait by optimising executive gait control while DBS of the PPN appeared to restore autonomic gait control. These results have several implications for DBS patient selection, surgical targeting, and for understanding the mechanisms underlying DBS efficacy.